Preferensi Peternak Terhadap Penggunaan Teknologi Inseminasi Buatan Pada Program Sapi Kerbau Komoditas Andalan Negeri (SIKOMANDAN): Breeders' Preferences for the Use of Artificial Insemination Technology In the National Mainstay Commodity Buffalo Cattle Program (SIKOMANDAN) (Jurnal Riset Agribisnis dan Peternakan, 2024)
This research aims to determine the characteristics of cattle breeders in Jogoresan Village, Purwodadi District, Purworejo Regency and the breeders' preferences for implementing the use of artificial insemination technology to support the National Mainstay Commodity Buffalo Cattle (SIKOMANDAN) program in Jogoresan Village, Purwodadi District, Purworejo Regency. Data collection uses questionnaires and Likert Scale. Data analysis uses quantitative descriptive analysis. The results of the research show that: the characteristics of breeders in Jogoresan Village, Purwodadi District, Purworejo Regency are based on age, education level, occupation and gender. Breeders' preferences are in the very high category, these preferences are seen from 5 main variables with an average of 88.46%. Shows that the SIKOMANDAN program has a very high influence on breeders in Jogoresan Village, Purwodadi District, Purworejo Regency.
Keywords: Preference; cattle farmer; artifiliacial inseminator; SIKOMANDAN